Accounting for Waqf Institutions: Business, Not-for-Profit or Hybrid Entities? - Umar, Umar Habibu; Haron, Md Harashid (International Journal of Islamic Economics and Finance (IJIEF), 2021)
Despite the tremendous religious and socio-economic contributions of waqf institutions to Muslim communities across the globe, there was no universal accounting standard to adopt by such institutions until 15 Rabiâ€™II (equivalent to 30th November 2020) when the Accounting Standard for waqf institutions (FAS No. 37) was approved by the Board of Accounting and Auditing Organization for Islamic Financial Institutions (AAOIFI) for adoption with effect from 01 January, 2022. Hence, the objective of this study is to analyze the nature of waqf institutions with a view to establishing whether their appropriate financial accounting and reporting practices should be for business, not-for-profit or both. The documentary research method was applied to achieve the aim of this study through a systematic analysis of relevant accounting and ShariÃ¡h standards. Findings and views of earlier studies were also used. The study reveals that though waqf institutions operate like charitable organizations, they are mandated to undertake or attach to commercial activities in order to generate income for the sustainability of their activities. This signified that they are hybrid and as such, they are supposed to report both waqf and commercial activities in their annual reports and accounts. Hence, the study calls on Islamic countries to provide regulations, guidelines and more importantly accounting standards that will compel or motivate waqf institutions to prepare annual reports and accounts showing both their charitable and commercial activities.Â